PENINGKATAN PRESTASI BELAJAR SISWA DALAM KONSEP SAINS DENGAN MENGGUNAKAN METODE EKSPERIMEN - Alfiati Syafrina (JURNAL FISIKA EDUKASI, 2015)
This study aims to: (1) to determine the activity of students in the implementation of the Science concept used an experimental method; (2) to determine the activity of teachers manage learning using the experimental method; and (3) to determine the presence / absence of increased student achievement using the experimental method. This type of research is classroom action research (PTK). Subjects in this study fourth grade students meunasah Tutong many as 30 people. Data analysis using descriptive statistics with a percentage formula. Based on the analysis of data obtained: (a) Activities of students in the following study used an experimental method in cycle 1 with an average score of 2.5 with less criteria, the second cycle an average score of 3.5 with sufficient criteria, and the third cycle an average score of 4.5 with good criteria; (B) Activities of teachers manage the learning using the experimental method in cycle 1 with an average score of 2.69 with less criteria, the second cycle an average score of 3.85 with both criteria, and the third cycle an average score of 4, 35 with good criteria; and (c) Student achievement in cycle 1 with an average value of 63, the second cycle with an average score of 71.33, and the third cycle with an average value of 80.33. Conclusion The experimental method could increase the activity of students during the learning progresses, the activity of teachers in managing learning, and students' science learning achievement.